The Strategy Of The Boarding School Student Organization In Developing The Leadership Spirit Of Students - Karimah, Ummah; Nurkholis, Alwi; Aulia, Muhammad Hanif; Fitriansyah, Mahliga (Indonesia, 2024)
The research aims to explain the strategy of the boarding school student organization in developing leadership skills. This research is qualitative research with descriptive method. The primary data source comes from the management of the Pondok Yatim Assa'adah Student Organization (OPPYA), which is a 6th grade TMI student at the Pesantren Yatim and Dhuafa' Assa'adah 1 South Jakarta. While secondary data comes from the results of interviews along with documentation obtained at the Pesantren Yatim and Dhuafa' Assa'adah 1 South Jakarta. The data analysis technique uses the flow method from Miles and Hubberman with stages, namely: (1) Data Reduction, (2) Data Presentation and (3) Conclusion Drawing. Data collection methods used interviews, observation and documentation. The main finding is that these strategies have a positive impact on the character building, leadership, and social skills of students especially in pesantren. In addition, the student organization also provides benefits to the pesantren in terms of administrative management and assisting social activities at the Pesantren Yatim and Dhuafa' Assa'adah 1 South Jakarta and to the community. The results of this study can provide valuable insights for pesantren and other Islamic educational institutions in developing student organization strategies more effectively. It can also serve as a basis for further research on the role of student organizations in the context of traditional Islamic education.